De novo biosynthesis of cytokinins in the biotrophic fungus Claviceps purpurea - Hinsch, Janine; Vrabka, Josef; Oeser, Birgitt; Novák, Ondřej; Galuszka, Petr; Tudzynski, Paul (Environmental microbiology, 2015)
Disease symptoms of some phytopathogenic fungi are associated with changes in cytokinin (CK) levels. Here, we show that the CK profile of ergot-infected rye plants is also altered, although no pronounced changes occur in the expression of the host plant's CK biosynthesis genes. Instead, we demonstrate a clearly different mechanism: we report on the first fungal de novo CK biosynthesis genes, prove their functions and constitute a biosynthetic pathway. The ergot fungus Claviceps purpurea produces substantial quantities of CKs in culture and, like plants, expresses enzymes containing the isopentenyltransferase and lonely guy domains necessary for de novo isopentenyladenine production. Uniquely, two of these domains are combined in one bifunctional enzyme, CpIPT-LOG, depicting a novel and potent mechanism for CK production. The fungus also forms trans-zeatin, a reaction catalysed by a CK-specific cytochrome P450 monooxygenase, which is encoded by cpp450 forming a small cluster with cpipt-log. Deletion of cpipt-log and cpp450 did not affect virulence of the fungus, but Δcpp450 mutants exhibit a hyper-sporulating phenotype, implying that CKs are environmental factors influencing fungal development.
Keywords: Isopentenyladenosine; Genes, Fungal; cytokininy; žito; Genes, Plant; Cytokinins; Alkyl and Aryl Transferases; Secale; delece genu; geny hub; alkyltransferasy a aryltransferasy; Cytochrome P-450 Enzyme System; Gene Deletion; systém (enzymů) cytochromů P-450; rostlinné geny; isopentenyladenosin; Claviceps